Octopus Pie. Volume 1 - Gran, Meredith, 1984- (Image Comics, 2016)
"Follow the adventures of two Brooklynites--Eve, a nerdy acerbic twentysomething, and her room-mate Hanna, a long-lost friend who's blossomed into happy-go-lucky stoner. Crazed childhood rivals, art world hipsters, Eve's meddlesome mom, and romances past and present crowd their odd yet ordinary lives"--Page 4 of cover.